DESCRIPTIVE STUDY ON WORK STRESS LEVEL OF INDOMARET’S EMPLOYEES IN BENGKALIS SUBDISTRICT - Lisda Br Sihombing; Bustami Bustami (Politeknik Negeri Bengkalis, 2022)
This study aims to determine the level of work stress of indomaret’s employees in Bengkalis subdistrict, as well as to determine the most dominant and least dominant factors affecting the work stress level of Indomaret’s employees. This study uses qualitative data. The population in this study were indomaret’s employees who work in indomaret in Bengkalis subdistrict, while the samples of study are 43 samples (employees). The data collection technique of this research used a questionnaire technique. This research uses non-probability sampling technique and type of research is survey research. The results of this study indicate that the factors that influence the work stress level of indomaret’s employees are Workload, Leader Attitude, Working Time, Conflict, Communication and Work authority. working time is the most dominant factor influencing the work stress level of indomaret’s employees in Bengkalis subdistrict with a score of 4.33 and the least dominant factor is the communication factor with a score of 3.82. <w:LsdEx